حوكمة النزاعات الاجتماعية الممتدة: بين إجراءات بناء السلام وطرق الأقلمة - بلغالم, امال; كواشي, عتيقة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يهدف المقال لتوضيح أدوار الحوكمة الأمنية العالمية في سياق بناء السلام المجتمعي إستنادًا لتبني نماذج نزاعات مجتمعية متعددة ، و ذلك انطلاقًا من فرضية الضعف الدولاتي في معالجة المشكلات المجتمعية المطروحة على الساحة الأمنية ، بما فيها مغذيات النزاع الداخلي ، وصولاً إلى حتمية تبني مقتربات تفاعلية تدمج في طياتها الفواعل الرسمية و غير الرسمية ، الحكومية و غير الحكومية ، المنظمات الدولية و غير الدولية ، العامة و الخاصة في شكل قولبة منهجية جد منظمة خاضعة لكل معايير الشفافية و الرقابة و الفاعلية الدولية و المجتمعية ، من خلال تحديد بؤر التوتر ، التدخل لتجسيد الدبلوماسية الوقائية ، صنع السلام ، التوجه نحو حفظ السلام ، و أخيرًا بناء السلام الإيجابي. This article aims at clarifying the global security governance in the context of community peace building according to adopting models of multiple societal conflicts and this on the basis of hypothesis of international weakness in solving societal problems raised on the security yard, including international conflicts of feeders to the invetability of adopting interactive proposals, combining formal & informal factors, governmental and non-governmental, international & non – international organizations, public and private. In the form of very organized methodical modeling subject to all standars of transparency and oversight, and international and societal efficacy by adjusting the stress points, intervention to materialize Preventive Diplomacy, Peace Making, Peace Keeping, and finally heading to Positive Peace Building